The influence of curing periods on the compressive strength of fly ash-based geopolymer at different aging times - Omar A., Abdulkareem; Mohd Mustafa Al-Bakri, Abdullah; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Khairul Nizar, Ismail, Prof. Madya Dr. (Trans Tech Publications, 2013)
Link to publisher's homepage at http://www.ttp.net/